2011
DOI: 10.1143/apex.4.106401
|View full text |Cite
|
Sign up to set email alerts
|

Europium and Sodium Codoped LiCaAlF$_{6}$ Scintillator for Neutron Detection

Abstract: A recent study has revealed that a Eu-doped LiCaAlF6 (Eu:LiCAF) crystalline scintillator showed good scintillation response under thermal neutron exposure. We discover here that Eu and Na codoped LiCAF exhibits superior scintillation properties to Eu:LiCAF. We grew Eu 2% and Na 0.5, 1, and 2% codoped LiCAF by the micropulling down method. In radioluminescence spectra, they showed intense emission peaking at 370 nm due to Eu2+ 5d–4f transition. In particular, the light yield of Eu 2% Na 2%-doped LiCAF reached 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 21 publications
0
32
0
1
Order By: Relevance
“…During the R&D processes, we found that the light yield can be enhanced by co-doping with alkali metal elements. 144) Alkali metal ions including Na, K, Rb and Cs are known to show no luminescence features. We discovered that, when Na is included to Eu-doped LiCaAlF 6 , the scintillation light yield was enhanced to ∼42,000 ph/n.…”
Section: Recent Randd Progress Of Scintillatorsmentioning
confidence: 99%
“…During the R&D processes, we found that the light yield can be enhanced by co-doping with alkali metal elements. 144) Alkali metal ions including Na, K, Rb and Cs are known to show no luminescence features. We discovered that, when Na is included to Eu-doped LiCaAlF 6 , the scintillation light yield was enhanced to ∼42,000 ph/n.…”
Section: Recent Randd Progress Of Scintillatorsmentioning
confidence: 99%
“…The GS20 glass scintillator is nonhygroscopic and shows an acceptable light yield (~6000 photons/neutron). In recent years, we have developed LiCaAlF 6 :Eu, (16)(17)(18)(19)(20) which shows nonhygroscopicity and higher light yield (typically ~20000 photons/neutron) than that of GS20. We describe the characteristics of a LiF:W (LiF doped with WO 3 ) single crystal as a thermal-neutron scintillator.…”
Section: Introductionmentioning
confidence: 99%
“…In medical applications, heavy scintillators are preferable to detect X-and -ray efficiently. For well-logging, sometimes neutron detectors are utilized and scintillators for neutron detection are generally light metarials such as 6 Li-glass [7][8] (product of Saint Gobain) or 6 LiCaAlF 6 [9][10] (product of Tokuyama Corp.) to suppress -ray environmental background noise.…”
Section: Introductionmentioning
confidence: 99%